Primary Absolute Cardiovascular Disease Risk and Prevention in Relation to Psychological Distress in the Australian Population: A Nationally Representative Cross-Sectional Study - Welsh, Jennifer; Korda, Rosemary J.; Joshy, Grace; Banks, Emily (Frontiers in Public Health, 2019)
People who experience psychological distress have an elevated risk of incident cardiovascular disease (CVD). The majority of CVD events can be prevented and current guidelines recommend an absolute risk approach. Despite the known association between psychological distress and CVD, population-level data on CVD risk profiles and appropriate management of risk in relation to distress are currently not available. The aim of this study was to use nationally representative data to quantify absolute risk of a primary CVD event, biological and behavioural risk factors, assessment and appropriate treatment of absolute risk according to level of psychological distress in the Australian population. Data were from 2618 participants aged 45-74 years without prior CVD who participated in the 2011-12 Australian Health Survey, a cross-sectional and nationally representative study of Australian adults. Age-and sex-adjusted prevalence of 5-year absolute risk of primary CVD (low <10%, moderate 10-15%, or high >15%), CVD risk factors, blood-pressure and cholesterol assessments, and appropriate treatment (combined blood pressure- and lipid-lowering medication) if at high primary risk, were estimated. Prevalence ratios (PR) quantified variation in these outcomes in relation to low (Kessler-10 score: 10-<12), mild (12-<16), moderate (16-<22) and high (22-50) psychological distress, after adjusting for sociodemographic characteristics. The prevalence of high absolute risk of primary CVD for low, mild, moderate and high distress was 10.9%, 12.3%, 11.4% and 18.6%, respectively, and was significantly higher among respondents reporting high compared to low distress (adjusted PR:1.62, 95%CI:1.04-2.52). The prevalence of CVD risk factors was generally higher in those reporting higher psychological distress. Blood pressure and cholesterol assessments were reported by the majority of respondents (>85%) but treatment of high absolute risk was low (<30%), and neither were related to psychological distress. Our findings confirm the importance of recognising people who experience psychological distress as a high risk group and highlight the unmet potential in Australia to reduce primary CVD events through appropriate management of high absolute risk.